Building a smart rehabilitation delivery platform with hybrid matching algorithm based on long-term care plan in Taiwan. (22nd June 2021) - Hung, Lun-Ping; Chen, Chien-Liang; Chang, Ruay-Shiung; Hsu, Yu-Chen
The smart rehabilitation care is to use information and communication technology to apply innovative services on patient care activities. In Taiwan, to solve the over lacking problem of rehabilitation treatment service for long-term care patient in general hospitals, the rehabilitation service delivery method has moved from centralised hospital-based treatment to decentralised community- or home-based rehabilitation. Therefore, community- or home-based long-term care patient has created huge amount of needs for rehabilitation service. To create a more efficient and friendly health care service model, this study uses a hybrid matching algorithm to construct a community and home-based smart rehabilitation service mechanism that allows both therapists and patients to find the most suitable service by setting up the matching parameters. This mechanism records rehabilitation activity, user's feedback, and suggestions from rehabilitation practitioners and can provide information to health units for follow-up treatment recommendation to achieve the goal of optimising long-term care service quality.